2017
DOI: 10.1186/s12874-017-0394-5
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of a Malay version of the brief illness perception questionnaire for patients with type 2 diabetes mellitus

Abstract: BackgroundIllness perceptions involve the personal beliefs that patients have about their illness and may influence health behaviours considerably. Since an instrument to measure these perceptions for Malay population in Malaysia is lacking, we translated and examined the psychometric properties of the Malay version of the Brief Illness Perception Questionnaire (MBIPQ) in adult patients with type 2 diabetes mellitus.MethodsThe MBIPQ has nine items, all use a 0–10 response scale, except the ninth item about cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 50 publications
5
40
1
1
Order By: Relevance
“…Stepwise linear regression analysis showed that illness perception had a significant influence on overall total SM as well as on communication with HCPs, problem‐solving, self‐integration and SMBG. Thus, illness perception was positively associated with overall SM and its dimensions, which echoes the findings of Chew et al () and Figueiras and Alves () that patients with threatening illness perception had better SM behaviour. However, this finding contradicts that of a study on T2DM (Kugbey et al, ) that persons who perceived their diabetes as more life‐threatening tended to participate in fewer self‐care practices.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Stepwise linear regression analysis showed that illness perception had a significant influence on overall total SM as well as on communication with HCPs, problem‐solving, self‐integration and SMBG. Thus, illness perception was positively associated with overall SM and its dimensions, which echoes the findings of Chew et al () and Figueiras and Alves () that patients with threatening illness perception had better SM behaviour. However, this finding contradicts that of a study on T2DM (Kugbey et al, ) that persons who perceived their diabetes as more life‐threatening tended to participate in fewer self‐care practices.…”
Section: Discussionsupporting
confidence: 87%
“…Stepwise linear regression analysis showed that illness perception had a significant influence on overall total SM as well as on communication with HCPs, problem-solving, self-integration and SMBG. Thus, illness perception was positively associated with overall SM and its dimensions, which echoes the findings of Chew et al (2017)…”
Section: Illness Perceptionsupporting
confidence: 80%
“…Scores range from 0 to 27 and are classified as minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe depressive symptoms (20)(21)(22)(23)(24)(25)(26)(27) [16,17]. Scores range from 0 to 27 and are classified as minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), moderately severe (15)(16)(17)(18)(19), and severe depressive symptoms (20)(21)(22)(23)(24)(25)(26)(27) [16,17].…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…The validated Malay Brief Illness Perception Questionnaire (MBIPQ) [18] has nine items that provide simple and rapid assessment of illness perceptions. It measures participants' cognitive and emotional representations of their illness, including consequences, timeline, personal control, treatment control, identity, concern, understanding, emotional response and causes.…”
Section: Illness Perceptionmentioning
confidence: 99%
See 1 more Smart Citation